2010
DOI: 10.1186/1471-2407-10-238
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses IGF-1 induced human colon cancer cell proliferation and elevates apoptosis via suppression of IGF-1R/Wnt and activation of p53 signaling pathways

Abstract: BackgroundObesity is a global phenomenon and is associated with various types of cancer, including colon cancer. There is a growing interest for safe and effective bioactive compounds that suppress the risk for obesity-promoted colon cancer. Resveratrol (trans-3, 4', 5,-trihydroxystilbene), a stilbenoid found in the skin of red grapes and peanuts suppresses many types of cancers by regulating cell proliferation and apoptosis through a variety of mechanisms, however, resveratrol effects on obesity-promoted colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(165 citation statements)
references
References 62 publications
2
160
0
3
Order By: Relevance
“…Results of the present study demonstrated that RES effectively inhibited the cell proliferation increased by EDCs on BG-1 cells expressing both ERs by inducing cell cycle arrest. From previous studies, RES is known for exerting antitumorigenic effects by suppressing cell proliferation and inducing apoptosis in various cancer cells, such as colon and pancreatic cancer cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study demonstrated that RES effectively inhibited the cell proliferation increased by EDCs on BG-1 cells expressing both ERs by inducing cell cycle arrest. From previous studies, RES is known for exerting antitumorigenic effects by suppressing cell proliferation and inducing apoptosis in various cancer cells, such as colon and pancreatic cancer cells (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…레스베라트롤(resveratrol)은 피토알렉신(phytoalexin)의 일종인 파이토케미컬로 포도껍질에 존재하며 레드와인과 포 도주스에 다량 함유되어 있다 [18]. 레스베라트롤은 암발생이 진행 중인 세포활동을 방해함으로써 항암작용을 하며, 심혈관 질환 예방에도 효과가 있는 것으로 알려져 있다 [12].…”
Section: 서 론unclassified
“…레스베라트롤은 암발생이 진행 중인 세포활동을 방해함으로써 항암작용을 하며, 심혈관 질환 예방에도 효과가 있는 것으로 알려져 있다 [12]. 최근에는 레스베라트롤이 전립선암에서 apoptosis를 유발하여 암세포 의 성장을 억제하며 [1], 대장암에서도 IGF-1R/Akt/Wnt 신호 경로의 억제와 p53의 활성화를 통해 apoptosis를 유도하는 것 으로 보고되었다 [18]. mTOR (Mammalian target of rapamycin)는 serin-threonine kinase의 일종으로 단백질 번역, 세포 성장, 증식 등의 물질대사 조절에서 중요한 역할을 하는 것으로 알려져 있다 [5].…”
Section: 서 론unclassified
“…Resveratrol may affect all three discrete stages of carcinogenesis (initiation, promotion, and progression) by modulating signal transduction pathways that control cell division and growth, apoptosis, inflammation, angiogenesis, and metastasis (Bishayee, 2009 ). Recently, it has been shown that resveratrol suppresses IGF-1 induced cell proliferation and elevates apoptosis in human colon cancer cells, via suppression of IGF-1R/Wnt and activation of p53 signaling pathways (Vanamala et al, 2010).…”
Section: Polyphenolic Compunds: Resveratrolmentioning
confidence: 99%